Analysis of Melanin Concentration on Reflective Pulse Oximetry Using Monte Carlo Simulations - Maximilian Reiser; Oliver Amft; Andreas Breidenassel (IEEE Access)
We investigate the impact of melanin concentration on the accuracy of oxygen saturation SpO2 estimation using reflective photoplethysmography (PPG) measurements. Monte Carlo (MC) simulations were used to analyse photon-tissue interactions, and detection of reflected light during systole and diastole. We model a reflective pulse oximeter and analyse the perfusion index (PI), to represent the signal change due varying blood flow during systole and diastole. Moreover, we derive the ratio-of-ratios (RoR), to represent the absorption difference between PIs of different light wavelengths, and SpO2 depending on skin tone. We derive calibration models for SpO2 estimation based on MC simulations tailored to specific melanin concentrations ranging from 2.55% to 30.5%, as well as a generalised population model, to study reflective pulse oximeter performance. While current pulse oximeters are often calibrated for low melanin concentrations, our results show that calibrating for an appropriate skin tone range substantially increases the pulse oximeter performance. Skin tone-adapted calibration reduced the root mean square error $A_{rms}$ of SpO2 estimation by 44% compared to a generalised population model. SpO2 estimation error was minimal at a distance of 4 mm to 5 mm between light source and photodetector of a reflective pulse oximeter. We conclude that skin tone-adapted calibration should be applied to make reflective pulse oximeter applicable to any human, independent of skin pigmentation.